The existence of To-Lotang as a religion in Bugis an anthropological perspective - Nursaadah, Takko Bandung, (Opción, 2019)
This study aims to reveal that To-Lotang religion in South Sulawesi Indonesia equals to other major religions and needs to be treated equally by the state. By using the qualitative method through observation in various social religious activities and in-depth interviews, this study found that the sustainability of the To-Lotang religion is more open and develops until today, as well as the follower’s increase. In conclusion, the To-Lotang religion has long existed in the land of Bugis, even before the major religions enter and thrive in the land of Bugis.